2014
DOI: 10.1617/s11527-014-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in the pozzolanic strength activity index (SAI) for silica fume according to EN and ASTM

Abstract: New supplementary cementitious materials claimed to possess pozzolan properties emerge frequently. This development is driven both by economic and environmental pressures. Properties of new materials are compared with those of materials already well known, such as silica fume. Several test methods are standardized for making such comparisons, regulated by both European (EN) and American (ASTM) standards. Standardization indicates that procedures are secured to make comparisons valid and informative. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 5 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…The slag is mainly (84.5 wt %) composed of silica (SiO 2 ), alumina (Al 2 O 3 ), and calcium oxide (CaO) components, while the HL is composed mainly (74.5 wt %) of CaO components, induced from Ca(OH) 2 and calcium carbonate (CaCO 3 ). SF has a bulk density of 200-350 kg/m 3 based on the manufacturer's material data sheet, and specific surface area of 15-30 m 2 /g based on the previous measurements [29]; it contains mainly silica (97 wt %), as shown in Table 1. In addition, Figure 1 shows the irregular shaped GGBFS particles, the plate-shaped Ca(OH) 2 in HL particles, and the perfectly globular SF particles.…”
Section: Methodsmentioning
confidence: 99%
“…The slag is mainly (84.5 wt %) composed of silica (SiO 2 ), alumina (Al 2 O 3 ), and calcium oxide (CaO) components, while the HL is composed mainly (74.5 wt %) of CaO components, induced from Ca(OH) 2 and calcium carbonate (CaCO 3 ). SF has a bulk density of 200-350 kg/m 3 based on the manufacturer's material data sheet, and specific surface area of 15-30 m 2 /g based on the previous measurements [29]; it contains mainly silica (97 wt %), as shown in Table 1. In addition, Figure 1 shows the irregular shaped GGBFS particles, the plate-shaped Ca(OH) 2 in HL particles, and the perfectly globular SF particles.…”
Section: Methodsmentioning
confidence: 99%
“…The CaCO 3 content in raw materials used for Ordinary Portland cement production is about 75 to 79 % [4], making partial replacement of clinker with supplementary cementitious materials (SCMs) a promising option for a more ecological production of concrete. Certain industrial by-products show encouraging results in the clinker substitution [5][6][7]. Fly ash from coal power plants and steel furnace slags have been broadly used as SCMs, but the reserves of these materials are not sufficient to satisfy the cement production demand.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the efficiency factor for SF concrete with all replacement levels is greater than 1 at 7 days. Recently Thorstensen and Fidjestol,(2015) studied the inconsistencies in the pozzolanic Strength Activity Index (SAI) for SF according to EN and ASTM [44].…”
Section: (24)mentioning
confidence: 99%